Impact of sandwiched strain periodic multilayer AlN GaN on strain and crystalline quality of a-plane GaN - Omar Ayad Fadhil Al-Zuhairi (Tanjong Malim, 2021)
Impact of sandwiched strain periodic multilayer AlN GaN on strain and crystalline quality of a-plane GaN by Omar Ayad Fadhil Al-Zuhairi